2008
DOI: 10.3921/joptom.2008.30
|View full text |Cite
|
Sign up to set email alerts
|

Visual Performance after AcrySof ReSTOR Aspheric Intraocular Lens Implantation

Abstract: RESUMEN OBJETIVO:Evaluar la calidad visual para visión lejana, intermedia y cercana en pacientes a los que se les ha implantado una lente intraocular (LIO) multifocal asférica AcrySof ReSTOR. MÉTODOS: Se midió la agudeza visual binocular con la mejor corrección (en inglés, BCVA) de alto y de bajo contraste [4 m], la agudeza visual cercana [40 cm] con la mejor corrección para lejos (en inglés, BCNVA), la agudeza visual intermedia [80 y 60 cm] con la mejor corrección para lejos, y la sensibilidad al contraste (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 23 publications
(43 reference statements)
7
36
1
1
Order By: Relevance
“…All these studies show that patients who received a hybrid multifocal IOL obtained better uncorrected near vision and distance-corrected near vision than those who received a monofocal IOL with no decrease in distance visual acuity. Obviously, as the authors pointed out, these findings show that patients with hybrid multifocal IOLs obtained a satisfactory full range of vision and achieved higher spectacle independence than those patients with monofocal IOLs, which is the reason 34 ReSTOR Aspheric 0.02 Ϯ 0.03* 0.0 Ϯ 0.04* Add +4.00 in emmetropia (46) Alfonso JF 35 ReSTOR aspheric ---0.005 Ϯ 0.08 -0.025 Ϯ 0.06 Add +4.00 (36) IOL = intraocular lens UCNV = uncorrected near vision; NV = distance-corrected near vision CTR = capsular tension ring. Table 2.…”
Section: Distance Intermediate and Near Visual Acuitymentioning
confidence: 95%
See 3 more Smart Citations
“…All these studies show that patients who received a hybrid multifocal IOL obtained better uncorrected near vision and distance-corrected near vision than those who received a monofocal IOL with no decrease in distance visual acuity. Obviously, as the authors pointed out, these findings show that patients with hybrid multifocal IOLs obtained a satisfactory full range of vision and achieved higher spectacle independence than those patients with monofocal IOLs, which is the reason 34 ReSTOR Aspheric 0.02 Ϯ 0.03* 0.0 Ϯ 0.04* Add +4.00 in emmetropia (46) Alfonso JF 35 ReSTOR aspheric ---0.005 Ϯ 0.08 -0.025 Ϯ 0.06 Add +4.00 (36) IOL = intraocular lens UCNV = uncorrected near vision; NV = distance-corrected near vision CTR = capsular tension ring. Table 2.…”
Section: Distance Intermediate and Near Visual Acuitymentioning
confidence: 95%
“…13 Montés-Micó and coauthors 13 reported that patients with multifocal IOLs had worse CSF under dim conditions. Studies evaluating the CSF after hybrid multifocal IOL implants 20,26,29,30,32,35,38,39,43,[46][47][48][49][50] also found a reduction in contrast sensitivity when the luminance level was reduced, particularly for higher spatial frequencies. This trend agrees with classic data on the effect of the luminance level on contrast sensitivity.…”
Section: Contrast Sensitivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Bifocal refractive (1)(2)(3) , diffractive (4)(5)(6)(7) , spherical hybrid (8)(9)(10)(11) and aspheric hybrid (12)(13)(14)(15)(16) IOLs generate two focal points along the optical axis to provide good monocular uncorrected distance and near visual acuity (UCVA and UNVA, respectively) as well as functional intermediate vision. The bifocal IOLs have also been implanted in RLE with good results at distance and near vision (17)(18)(19)(20)(21)(22)(23)(24)(25) .…”
Section: Introductionmentioning
confidence: 99%